2008
DOI: 10.1063/1.2821152
|View full text |Cite
|
Sign up to set email alerts
|

Materials characteristics and surface morphology of a cesium iodide coated carbon velvet cathode

Abstract: Cesium iodide (CsI) coated carbon fiber cathodes have shown promise as a cold cathode for microwave and x-ray devices. In particular, the cathodes have demonstrated over 1 000 000 shots lifetime at operating voltages at or in excess of 165 kV and current densities greater than 25A/cm2. While the vacuum emission characteristics have been well studied, the materials characteristics of the cathodes themselves, particularly after operation, have received little attention. Furthermore, while researchers at Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 8 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…Shiffler et al [13] has reported a reduction in outgassing and improved emission uniformity after CsI coatings on carbon fibers. Even two orders of magnitude reduction in turn-on voltage was successfully achieved by means of CsI coating on carbon fiber-based FE devices by the same group [14]. Due to the importance of CsI photocathodes, several thin film preparation methods, such as thermal evaporation [15,16], ion beam sputtering [17], e-gun evaporation [18], spray pyrolysis [19], pulsed laser deposition [20] are used to study the various physical and chemical properties of CsI.…”
Section: Introductionmentioning
confidence: 99%
“…Shiffler et al [13] has reported a reduction in outgassing and improved emission uniformity after CsI coatings on carbon fibers. Even two orders of magnitude reduction in turn-on voltage was successfully achieved by means of CsI coating on carbon fiber-based FE devices by the same group [14]. Due to the importance of CsI photocathodes, several thin film preparation methods, such as thermal evaporation [15,16], ion beam sputtering [17], e-gun evaporation [18], spray pyrolysis [19], pulsed laser deposition [20] are used to study the various physical and chemical properties of CsI.…”
Section: Introductionmentioning
confidence: 99%
“…7,14 More specifically, the aqueous spray coating deposition technique utilized to apply the CsI-containing coating on the fiber cathodes introduces both water as well as dispersed CsI in the fiber. 7,14 More specifically, the aqueous spray coating deposition technique utilized to apply the CsI-containing coating on the fiber cathodes introduces both water as well as dispersed CsI in the fiber.…”
Section: Resultsmentioning
confidence: 99%
“…5 Upon application of the CsIcontaining aqueous solution, the fibers are annealed to remove water and any other volatile adsorbents. 7 Such high levels of emitted current densities originating from field emission cathodes have generally been attributed to contributions from explosive field emission, 8 a process whereby excessive heating of the cathode leads to cathode material vaporization and plasma formation along the cathode surface. 6 Typical emitted current densities of 25 A / cm 2 at pulsed operation with applied voltages of 165 kV have been realized.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable experimental investigations were carried out on the emission characteristics of carbon fibers as field emitters under the external large electric field [13][14][15][16][17]. However, discusses on the property of carbon fibers, during the electrical explosion process, are scanty in the literature.…”
Section: Introductionmentioning
confidence: 98%